Transferable Antibiotic Resistances in Marketed Edible Grasshoppers (Locusta migratoria migratorioides). Issue 5 (24th March 2017) - Osimani, Andrea; Garofalo, Cristiana; Aquilanti, Lucia; Milanović, Vesna; Cardinali, Federica; Taccari, Manuela; Pasquini, Marina; Tavoletti, Stefano; Clementi, Francesca
Abstract: Grasshoppers are the most commonly eaten insects by humans worldwide, as they are rich in proteins and micronutrients. This study aimed to assess the occurrence of transferable antibiotic resistance genes in commercialized edible grasshoppers. To this end, the prevalence of 12 selected genes [ aac (6') ‐Ie aph (2″)‐ Ia, blaZ, erm (A), erm (B), erm (C), mecA, tet (M), tet (O), tet (S), tet (K), vanA, vanB ] coding for resistance to antibiotics conventionally used in clinical practice was determined. The majority of samples were positive for tet (M) (70.0%), tet (K) (83.3%) and blaZ (83.3%). A low percentage of samples were positive for erm (B) (16.7%), erm (C) (26.7%), and aac (6') ‐Ie aph (2″) ‐Ia (13.3%), whereas no samples were positive for erm (A), vanA, vanB, tet (O), and mecA . Cluster analysis identified 4 main clusters, allowing a separation of samples on the basis of their country of origin.